The expression of Th17/Treg in oral submucosal fibrosis carcinogenesis and the significance in the development of mucosal lesions: Th17/Treg and its relationship with oral carcinogenesis and lesion development - Wu, Dan; Liu, Xun; Zhou, Tingting; Tan, Jin (Cellular and Molecular Biology, 2023)
It targets to explore the expression of Th17/Treg in oral submucous fibrosis (OSF) carcinogenesis and its significance in the development of mucosal lesions. In this research, 100 patients with OSF who visited our hospital for surgical treatment from March 2020 to April 2022 were selected. Based on pathological examination results, the patients were divided into 27 patients with oral leukoplakia (OK) group, 14 patients with oral lichen planus (OLP) group, 9 patients with oral squamous cell carcinoma (OSCC) group, and 50 patients with OSF group. It adopted flow cytometry (FC) to calculate the ratio of peripheral blood Th17 cells and Treg cells in four groups, and the Th17/Treg ratio was calculated; The area of oral mucosal lesions (OML) from patients was collected. It needs to compare the differences in Th17/Treg ratio and OML area among four groups and determine the correlation between indicators. ROC curve was used to analyze the diagnostic threshold of the Th17/Treg ratio for carcinogenesis. Except for the OK and OLP, it had statistical significance differences in Th17, Treg cells, and Th17/Treg ratio (P<0.001); The area of OML in the OK, OLP, and OSCC was higher than that in the simple OSF, with statistical significance (P<0.001); Th17 (%), Treg (%), and Th17/Treg all had direct ratio with the area of OML; The area of OML has directed ratio with the development of mucosal lesions (r>0, P<0.05); The areas under the ROC curve for patients with OSF combined with OK, OLP, or OSCC with Th17 (%), Treg (%), Th17/Treg, and OML area were 0.560, 0.986, 0.936, and 0.466, respectively. The expression of Th17/Treg is elevated in oral submucosal fibrosis and carcinogenesis. When mucosal lesions progress or become cancerous, the Th17/Treg ratio increases accordingly, and it has more clinical value than the increase in the OML area.